Influence of in-situ and ex-situ HZSM-5 catalyst on co-pyrolysis of corn stalk and polystyrene with a focus on liquid yield and quality. (10th November 2019) - Muneer, Bushra; Zeeshan, Muhammad; Qaisar, Sara; Razzaq, Madiha; Iftikhar, Hera
Abstract: Catalytic and non-catalytic co-pyrolysis of Corn Stalk (CS) and Polystyrene (PS) was conducted in a fixed bed reactor at 500 ° C to evaluate the effect of feedstock blend ratio, catalyst to feedstock ratio (CFR) and mode of catalyst addition. In first phase, CS and PS were co-pyrolyzed in multiple blend ratios (1:0, 1:3, 1:1, 3:1, 0:1) without catalyst application. Increasing PS in blend increased oil yield, with a maximum synergistic value of 5.75 observed at CS:PS ratio of 1:3. In the second phase, comparison between in-situ and ex-situ use of HZSM-5 catalyst at five different CFR (1:10, 1:4, 1:2, 3:4 and 1:1) was explored. The in-situ mode yielded more liquid oil (maximum 66.5% at CFR 1:4) with higher (80.1% at CFR 1:2) mono aromatic hydrocarbons (MAH) and less (6.5% at CFR 1:10) poly aromatic hydrocarbons (PAH) and acids (4.6% at CFR 1:1). However, increasing CFR in twain modes decreased MAH and oxygenates and increased PAH and acids. Maximum aromatics selectivity to BTEX (∼100%) and negligible selectivity to styrene was noticed at ex-situ CFR of 1:1. Non-catalytic co-pyrolysis yielded maximum MAH (83%). Further physical analysis of non-catalytic co-pyrolysis oil showed properties of liquid oil close to conventional fossil fuels. Graphical abstract: Image 1 Highlights: CS:PS, 1:3 showed maximum synergetic effect in non-catalytic co-pyrolysis runs. Oil yield decreased with both, in-situ and ex-situ application of HZSM-5. Highest MAH were obtained in non-catalytic co-pyrolysis. PAH in oil increased and oxygenates decreased with catalyst to feedstock ratio. Non-catalytic pyrolysis oil showed characteristics comparable to diesel.